Guide for a Successful Doctoral Journey - Karannagoda, Neluka Maduranga; Aponsu, R.; Athukorala, L.H. (Nine Publishing, 2025)
Embarking on a doctoral journey is not for the faint-hearted. It is a challenging expedition that requires immense dedication, rigorous discipline, and an insatiable thirst for knowledge. This journey is not just about earning a title or a degree; it is about transforming into a scholar who contributes significantly to the existing body of knowledge in a chosen discipline. Welcome to "Guide for a Successful Doctoral Journey", which is a book that aims to provide a roadmap to navigate this challenging yet rewarding journey. This book, subtitled "Ten Golden Principles to be Followed by Any PhD Candidate", is a treasure trove of practical advice, valuable insights, and professional wisdom gathered from seasoned academics and successful PhD holders. It is designed to prepare you, a PhD candidate, for the trials and tribulations that you might encounter on your path to academic excellence. The ten golden principles outlined in this book are not just theoretical concepts but are tried and tested strategies that have helped many to complete their doctoral journey successfully. These principles cover a wide range of topics, from choosing the right research topic, managing time efficiently, and dealing with academic stress to successfully defending your thesis. This book is not a mere guide, it is a companion that will stay with you throughout your doctoral journey, providing guidance, motivation, and support when you need it the most. By following these principles, you will not only be able to complete your PhD successfully but will also enjoy the journey and grow personally and professionally. Remember, the journey of a thousand miles begins with a single step. Let this book be your first step toward a successful doctoral journey. Welcome aboard!
10 Golden Principles Which be Key to any Ph.D. Candidate
Guide for a Successful Doctoral Journey, 2nd Edition, co-authored by Dr. N. M. Karannagoda, Professor Rasika Aponsu, and Ms. L. H. K. Athukorala, is an invaluable resource for anyone pursuing a doctoral degree. This practical guide offers step-by-step advice and strategies to navigate the challenges of a PhD journey, making it an essential companion for achieving academic success.
Keywords: PhD; Doctoral; Guide; Doctoral Journey; Management; Research